Genome-wide analysis and expression profile of the bZIP gene family in Neopyropia yezoensis - Zhu, Xinyu; Gao, Tian; Bian, Ka; Meng, Chengzhen; Tang, Xianghai; Mao, Yunxiang (Frontiers in Plant Science, 2024)
The basic leucine zipper (bZIP) family consists of conserved transcription factors which are widely present in eukaryotes and play important regulatory roles in plant growth, development, and stress responses. Neopyropia yezoensis is a red marine macroalga of significant economic importance; however, their bZIP family members and functions have not been systematically identified and analyzed. In the present study, the bZIP gene family in Ny. yezoensis was characterized by investigating gene structures, conserved motifs, phylogenetic relationships, chromosomal localizations, gene duplication events, cis-regulatory elements, and expression profiles. Twenty-three Ny. yezoensis bZIP (NyybZIP) genes were identified and sorted into 13 out of 30 groups, which were classified based on the bZIPs of Ny. yezoensis and 15 other red algae species. Phylogenetic analysis revealed that bZIP genes may have a complex evolutionary pattern in red algae. Cross-species collinearity analysis indicated that the bZIP genes in Ny. yezoensis, Neoporphyra haitanensis, and Porphyra umbilicalis are highly evolutionarily conserved. In addition, we identified four main categories of cis-elements, including development-related, light-responsive, phytohormone-responsive and stress-responsive promoter sequences in NyybZIP genes. Finally, RNA sequencing data and quantitative real-time PCR (qRT-PCR) showed that NyybZIP genes exhibited different expression patterns depending on the life stage. NyybZIP genes were also found to be involved in the nitrogen stress response. We thought that bZIP genes may be involved in Ny. yezoensis growth and development, and play a significant role in nitrogen deficiency response. Taken together, our findings provide new insights into the roles of the bZIP gene family and provide a basis for additional research into its evolutionary history and biological functions.